Misoprostol-induced fever and genetic polymorphisms in drug transporters SLCO1B1 and ABCC4 in women of Latin American and European ancestry. (June 2015) - Alfirevic, Ana; Durocher, Jill; Elati, Anisa; León, Wilfrido; Dickens, David; Rädisch, Steffen; Box, Helen; Siccardi, Marco; Curley, Paul; Xinarianos, George; Ardeshana, Arjun; Owen, Andrew; et al.
Aim: Misoprostol, a prostaglandin analogue used for the treatment of postpartum hemorrhage and termination of pregnancy, can cause high fevers. Genetic susceptibility may play a role in misoprostol-induced fever.Subjects & methods: Body temperature of women treated with misoprostol for termination of pregnancy in the UK (n = 107) and for postpartum hemorrhage in Ecuador (n = 50) was measured. Genotyping for 33 single nucleotide polymorphisms in 15 candidate genes was performed. Additionally, we investigated the transport of radiolabeled misoprostol acid across biological membranes in vitro .Results: The ABCC4 single nucleotide polymorphism rs11568658 was associated with misoprostol-induced fever. Misoprostol acid was transported across a blood–brain barrier model by MRP4 and SLCO1B1.Conclusion: Genetic variability in ABCC4 may contribute to misoprostol-induced fever in pregnant women. Original submitted 21 January 2015; Revision submitted 24 April 2015